THE ROLE OF STRATEGIC ENTREPRENEURSHIP IN EFFORT TO DEVELOP BUSINESS SOCIETY: A LITERATURE REVIEW - Husriadi, Muh. (Journal of Finance, Economics and Business, 2023)
Strategic Entrepreneurship has emerged as a new concept in convergence studies in entrepreneurship research (opportunity-seeking behavior) and strategic management (profit-seeking behavior). Research in the field of strategic management is gradually uncovering the relationship between strategic management and entrepreneurship. Developing an entrepreneurial strategy. intrapreneurship. Entrepreneurial strategic attitudes in organizations. Entrepreneurial orientation; integration of strategic management as a context for entrepreneurial activity. Entrepreneurship theory with strategic management and resource-based perspectives. Ireland et al. Conceptual models developed for strategic entrepreneurship suggest that firms engage in linear, sequential actions that include: Manage resources strategically to exploit opportunities. Leveraging creativity and innovation to create competitive advantage is a strategic and entrepreneurial activity. Managers must maximize results and exploit competitive advantages while maximizing new business opportunities to create sustainable shareholder value. In this article, we develop a conceptual framework that describes the role of strategic entrepreneurship in efforts to develop community businesses.